Speed Machines - Graham, Ian (Miles Kelly Publishing Ltd. Essex, 2014)
Bursting with astounding facts and striking photographs, this gripping series concentrates on only the most amazing content, from record breaking vehicles to the deadliest predators. Short paragraphs encourage reluctant readers. Inventive design and fantastic images.
Keywords: Technology